2021
DOI: 10.22331/q-2021-05-10-455
|View full text |Cite
|
Sign up to set email alerts
|

Multi-time correlations in the positive-P, Q, and doubled phase-space representations

Abstract: A number of physically intuitive results for the calculation of multi-time correlations in phase-space representations of quantum mechanics are obtained. They relate time-dependent stochastic samples to multi-time observables, and rely on the presence of derivative-free operator identities. In particular, expressions for time-ordered normal-ordered observables in the positive-P distribution are derived which replace Heisenberg operators with the bare time-dependent stochastic variables, confirming extension of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 145 publications
1
4
0
Order By: Relevance
“…Indeed, such a reduction of depletion was observed, strongly supporting the hypothesis that adiabaticity is needed for agreement with the results of [33]. More detailed study of this will be reported in [68].…”
Section: Simulation Typessupporting
confidence: 82%
See 3 more Smart Citations
“…Indeed, such a reduction of depletion was observed, strongly supporting the hypothesis that adiabaticity is needed for agreement with the results of [33]. More detailed study of this will be reported in [68].…”
Section: Simulation Typessupporting
confidence: 82%
“…However, over adiabatic timescales, this still introduced far too much noise in the Bogoliubov fields ψ B , ψ B to be useful. fact that an instantaneous quantum quench of a weakly interacting condensate produces depletion with a similar time-integrated momentum profile dt n B (k, t) ∝ 1/k 4 to the ground state value, but with a somewhat higher depletion, as described in detail in [68,78]. Simulations show that non-instantaneous but rapid quenches produce lower amounts of quantum depletion, as shown in Fig.…”
Section: B Initial Conditionmentioning
confidence: 65%
See 2 more Smart Citations
“…We used the robust stochastic integration procedure described in Ref. 82 . The and are independent white Gaussian noise fields of zero mean and variance: …”
Section: Methodsmentioning
confidence: 99%